2006
DOI: 10.1039/b601840h
|View full text |Cite
|
Sign up to set email alerts
|

Metal-based antitumour drugs in the post genomic era

Abstract: The discovery of new metal-based antitumour drugs, whether cisplatin derivatives or those based on other metals, has been largely based on cell viability assays (IC50 values) and compounds that bind to DNA. This approach has been applied for more than 30 years during which time very few new drugs have entered clinical use. In this article we discuss what the future holds for metal-based drugs, in particular anti-metastasis drugs, in these enlightened times of the post genomic era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
525
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 737 publications
(543 citation statements)
references
References 39 publications
2
525
0
15
Order By: Relevance
“…Additionally, the products of reaction 1, corresponding to electrontransfer, may also arise via charge-transfer at a crossing point without proceeding through a long-lived complex. Previous ion/ion reaction studies involving multiply charged ions have suggested that charge-transfer at crossing points without long-lived complex formation can contribute significantly, in at least some cases, to electron-transfer [13][14][15]. Reactions 2 and 3, on the other hand, are expected to proceed via a long-lived complex.…”
Section: Computational Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the products of reaction 1, corresponding to electrontransfer, may also arise via charge-transfer at a crossing point without proceeding through a long-lived complex. Previous ion/ion reaction studies involving multiply charged ions have suggested that charge-transfer at crossing points without long-lived complex formation can contribute significantly, in at least some cases, to electron-transfer [13][14][15]. Reactions 2 and 3, on the other hand, are expected to proceed via a long-lived complex.…”
Section: Computational Chemistrymentioning
confidence: 99%
“…Ruthenium(II) complexes have been extensively examined as spectroscopic probes of local DNA structure [11,12]. The mechanism of action of the chemotherapeutic agent cisplatin involves binding to DNA to prevent replication [13][14][15]. Mass spectrometry has been used as a tool for the examination of ODN complexes with metal ions [16].…”
mentioning
confidence: 99%
“…These complexes selectively bind to proteins or inhibit enzymes known to be overexpressed in many types of cancer. 7,[9][10][11][12][13] To date, much work has been done to elucidate the mode of action of various ruthenium-based drug candidates, 14,15 but the way they exert their antitumoural or antimetastatic effects is not yet fully understood, even for NAMI-A and NKP-1339, which have successfully completed clinical trials. 14,[16][17][18] By analogy with platinum complexes, it was originally assumed that DNA binding was the main reason for the anticancer activity of ruthenium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Ruthenium compounds are currently considered the most likely candidates for the next generation of metal-based anticancer drugs [2,3]. Two representatives of this class of compounds have entered clinical trials so far: imidazolium trans-[tetrachlorido(dimethylsulfoxide)(1H-imidazole)ruthenate(III)] (NAMI-A) [4,5] and indazolium trans-[tetrachloridobis(1H-indazole)ruthenate(III)] (KP1019) [6][7][8] (see Chart 1 for structures).…”
Section: Introductionmentioning
confidence: 99%